In Defence of State Directed Enhancement. Issue 1 (16th June 2014) - Fowler, Tim
Abstract This article considers the ways in which a liberal society ought to view the potential to cognitively or physically enhance children. At present, the dominant approach in the literature is to leave this decision to parents. I suggest that the parental choice approach is often inadequate and fails to account properly for the interests of children and wider society in enhancement decisions. Instead I suggest that the state should play a greater role in determining when, and how, to enhance. To make this case, I compare the case of enhancement with existing practices of education, an area in which the state already plays a significant role. Finally I suggest that some concerns with a statist approach are not as serious as has been argued.